The Development of Al18F-NOTA-FAP-2286 as an FAP-Targeted PET Tracer and the Translational Application in the Diagnosis of Acquired Drug Resistance in Progressive Prostate Cancer - Xia Du; Yu Zhang; Yao Jia; Bo Gao (Pharmaceutics)
Objectives: Tumor heterogeneity and acquired resistance to prostate-specific membrane antigen (PSMA) radioligand therapy (PRLT) pose significant challenges to PSMA PET-based diagnosis. This study aimed to develop an Al18F-labeled FAP-targeted tracer and explore the diagnostic value in acquired drug-resistant tumor models. Methods: To identify potential targets for imaging drug-resistant prostate cancer, bioinformatic analysis was employed to correlate FAP expression levels with genes associated with tumor progression and radiotherapy resistance. Molecular docking technology simulations were utilized to screen FAP ligands for optimal binding affinity and target specificity. The most promising ligand, FAP-2286, was radiolabeled with 18F to develop a novel PET imaging agent, Al18F-NOTA-FAP-2286 PET. To evaluate the diagnostic potential of this agent, various tumor models were established. U87 cells were used to optimize the imaging protocol and assess targeting efficiency and 22RV-1-resistant cells co-xenografted with NIH-3T3 cells were used to model acquired drug-resistant prostate cancer. The diagnostic efficacy of Al18F-NOTA-FAP-2286 PET in this acquired drug-resistant model was assessed and validated through immunohistochemical staining of tumor tissue. Results: Bioinformatic analysis confirmed the association between FAP expression and key genes involved in radiotherapy resistance, such as HIF1α, BCL2, ATM, and EGFR. Molecular docking studies demonstrated the strong binding affinity of FAP-2286 to FAPα (−10 kcal/mol). Al18F-NOTA-FAP-2286 PET/CT imaging in U87 tumor-bearing mice revealed accurate targeting of high FAP-expressing xenografts. The imaging characteristics of Al18F-NOTA-FAP-2286 were comparable to 18F-FDG and 68Ga-FAP-2286 but with a prolonged imaging window compared to 68Ga-FAP-2286. In acquired drug-resistant prostate cancer xenograft nude mice, Al18F-NOTA-FAP-2286 could effectively detect tumor lesions, as confirmed by immunohistochemical analysis. Conclusions: Al18F-NOTA-FAP-2286, as a PSMA-independent imaging agent, holds promise as a valuable complementary molecular imaging tool for assessing acquired resistance to PRLT.